The data integrity problem and multi-layered document integrity - Moss, Ben (2007)
Data integrity is a fundamental aspect of computer security that has attracted much interest in recent decades. Despite a general consensus for the meaning of the problem, the lack of a formal definition has led to spurious claims such as "tamper proof", "prevent tampering", and "tamper protection", which are all misleading in the absence of a formal definition.